Update in understanding common variable immunodeficiency disorders (CVIDs) and the management of patients with these conditions. - Chapel, H; Cunningham-Rundles, C (2009)
The common variable immunodeficiency disorders are a mixed group of heterogeneous conditions linked by lack of immunoglobulin production and primary antibody failure. This variability results in difficulty in making coherent sense of either immunopathogenesis or the role of various genetic abnormalities reported in the literature. The recent attempt to collate the varied complications in these conditions and to define particular clinical phenotypes has improved our understanding of these diseases. Once refined and confirmed by other studies, these definitions will facilitate improved accuracy of prognosis and better management of clinical complication. They may also provide a method of analysing outcomes as related to new immunopathological and genetic findings.